2019
DOI: 10.1016/j.pmrj.2018.08.380
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Isokinetic Muscle Strength of Athletes Involved in Sports Characterized by Constantly Varied Functional Movements Performed at High Intensity: A Cross‐Sectional Study

Abstract: These data from highly trained FMHI athletes can be compared to that of other athletes to help determine individual weaknesses, strengths, and imbalances, and may be useful for designing training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
2
13
1
1
Order By: Relevance
“…The aim of the present study was to examine bilateral and ipsilateral knee isokinetic strength ratios in elite football players. 30 -1 angular velocity in the comparison of both ipsilateral H/Q and bilateral O/Q and H/H ratios (p<0,05). As a result, it was found that in elite football players, DT sides produced higher strength at all angular velocities when compared with NDT sides and both bilateral and ipsilateral strength differences were found at 60 o sn -1 angular velocity, which requires high strength.…”
Section: Investigation Of Bilateral and Ipsilateral Strength Ratios Imentioning
confidence: 90%
See 1 more Smart Citation
“…The aim of the present study was to examine bilateral and ipsilateral knee isokinetic strength ratios in elite football players. 30 -1 angular velocity in the comparison of both ipsilateral H/Q and bilateral O/Q and H/H ratios (p<0,05). As a result, it was found that in elite football players, DT sides produced higher strength at all angular velocities when compared with NDT sides and both bilateral and ipsilateral strength differences were found at 60 o sn -1 angular velocity, which requires high strength.…”
Section: Investigation Of Bilateral and Ipsilateral Strength Ratios Imentioning
confidence: 90%
“…Mevcut araştırmamızdaki futbolcuların bilateral kuvvet oranları literatüründe rapor edilen güvenilir aralıktadır.Araştırmamızda futbolcuların diz EKS ve FLEK kuvvetlerine bağlı lateral asimetri oranları konvensiyonel olarak Q ve H kasında Kon/Kon kasılmalarla alınmıştır. Ancak futbolun hareket yapısı gereği diz kuvvetinin fonksiyonel olarak yani Q kasında konsantrik, H kasında eksantrik değerlendirme adına daha geçerli bir yöntemdir[29,30]. Konvensiyonel olarak lateral asimetrik oranları değerlendirmek geçerli bir yöntem olsa da mevcut araştırmamızın fonksiyonel yöntemi içermemesi çalışmanın ana sınırlılıklarından biri olarak karşımıza çıkmaktadır.Sonuç olarak, araştırmamızda ki futbolcularda EKS fazında DT tarafın NDT'ye göre daha kuvvetli olduğu, FLEK fazında ise benzer sonuçlar ortaya çıkardığı görülmektedir.…”
unclassified
“…4 The isokinetic device's rotation axis was placed at the intersection of the mid-axillary line and the lumbosacral region, approximately 3.5 cm below the upper edge of the iliac crest. 5 Fix the subject's chest, pelvis and lower limbs. When the lower limbs are fixed, keep the vertebrae slightly flexed by 15°, allowing their range of motion to be between 80° flexion and 10° extension.…”
Section: Methods Treatment Methodsmentioning
confidence: 99%
“…36 Other studies have also used the same isokinetic test speeds for isokinetic strength evaluation. 28,29,32,33 The eccentric test consisted of five maximal repetitions at 240 deg/sec. Between sets, participants had 60 seconds of rest time.…”
Section: Isokinetic Strength Testmentioning
confidence: 99%